2016
DOI: 10.1002/eco.1793
|View full text |Cite
|
Sign up to set email alerts
|

Responses of fish and invertebrates to floods and droughts in Europe

Abstract: Floods and droughts, two opposite natural components of streamflow regimes, are known to regulate population size and species diversity. Quantifiable measures of these disturbances and their subsequent ecological responses are needed to synthesize the knowledge on flow-ecosystem relationships. This study for the first time combines the systematic review approach used to collect evidence on the ecological responses to floods and droughts in Europe with the statistical methods used to quantify the extreme events… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 98 publications
(108 reference statements)
2
44
0
1
Order By: Relevance
“…The actual response of the fish community to floods is, however, ambiguous (Piniewski et al 2017). Several studies reported that non-native species showed the most negative response to floods, which is usually explained by a lack of adaptation to flood regimes (Deboer et al 2011;Piniewski et al 2017). The non-native species in these studies were primarily salmonids, though.…”
Section: Generalmentioning
confidence: 76%
See 2 more Smart Citations
“…The actual response of the fish community to floods is, however, ambiguous (Piniewski et al 2017). Several studies reported that non-native species showed the most negative response to floods, which is usually explained by a lack of adaptation to flood regimes (Deboer et al 2011;Piniewski et al 2017). The non-native species in these studies were primarily salmonids, though.…”
Section: Generalmentioning
confidence: 76%
“…benthic, rocky habitats), were found to be not affected by floods or even increased in abundance afterwards (Deboer et al 2011;Jurajda et al 2006). Less is known on the effect of floods on early developmental stages, which appears to be also very variable and species-specific (Jurajda et al 2006;Piniewski et al 2017). There is indication that gobies react to perturbations by adapting life-history-traits, for instance by increasing oocytes number (Hôrková and Kováč 2015).…”
Section: Generalmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the conceptual model in Figure is generic and some studies have found different results for individual cases (Piniewski et al, ). One of the more significant covariates causing such deviations is the morphological variability of rivers and floodplains.…”
Section: Biological Responsementioning
confidence: 99%
“…; Maier ; Pupilli & Puig ; Suren & Jowett ; Death ; Molineri ; Lee & Bae ; Piniewski et al . ; Kim et al . ).…”
Section: Introductionunclassified